An investigation of the secure data communication in medical mobile applications - Aminnezhad, Asou; Abdullah @ Selimun, Mohd Taufik; Hezave, Pooya Khanmohamadi (Asian Research Publication Network, 2015)
Nowadays, medical applications (apps) have become a rapidly growing and basic tool in medical education, patient care and clinical research that are vitally important to aware people with a health signal. Similar to other sorts of telecommunication and Internet applications, the medical apps are vulnerable against attackers or unauthorized interceptions. An encryption is a common way to provide the privacy of medical application users. In this paper, we examine ten popular medical applications and analyze the intercepted communication to determine the encryption of captured packets and text communications based on obtained results.